Pengaruh Mengunyah Tebu (Saccharum Officinarum L.) dan Bengkuang (Pachyrhizus Erosus) Terhadap Perubahan Indeks Debris pada Anak Umur 8-9 Tahun di SD Adabiah Kota Padang - Dezy Adrianton; Sri Ramayanti; Reni Nofika (Andalas Dental Journal, 2019)
Debris is food residued that found on the surface of the teeth. Accumulation of debris will trigger plaque formation, causing dental caries. Debris surface area evaluated by using the debris index. One way to reduce the debris index is to eat foods that contain water and fiber such as cane and yam, because it can help the self-cleansing and stimulate salivary flow in the mastication process. The objective of the study was to find out the effect of cane and yam chewing to change the debris index in children aged 8-9 years at Adabiah Elementary School Padang. This study used a quasi experiment method with two group pretest and posttest design that used purposive sampling with a sample of 44 students and consisted of two treatment groups. Group 1 was given the instruction to chew cane in the first day and group 2 to chew yam in the second day. The results of the study is average debris index before and after chewing a cane decreased by 0,522 and chewing a yam decreased by 0,497. Paired T-Test test results showed the value of p=0.001 (p<0.05) between before and after treatment in each treatment groups. The Independent T-Test showed that the value of p=0.581 (p>0.05) between treatment groups. The Conclusion showed chewing cane and yam for children aged 8-9 years at Adabiah Elementary School Padang has an effect in decresing the debris index, but there is no significant change between both of them.